Вплив експериментального цукрового діабету на експресію транскрипційних факторів T-bet та GATA3 в лімфоїдних структурах клубової кишки щурів - Деген, Анна Сергіївна; Камишний, Олександр Михайлович; Деген, А. С.; Камышный, А. М.; Degen, A. S.; Kamyshny, A. M. (My University, 2013)
В експерименті досліджувався вплив експериментального цукрового діабету на інтенсивність експресії транскрипційних факторів T-bet та GATA імунними клітинами клубової кишки. Для визначення T-bet+ та GATA +-клітин було застосовано метод непрямої імунофлюоресценції з використанням моноклональних антитіл до T-bet та GATA щура. Встановлено, що розвиток діабету супроводжується збільшенням кількості T-bet+-клітин в лімфоїдних структурах кАлТ на 45-72% (р<0,05), зниженням сумарної щільності GATA3+-лімфоцитів на 21-44% (р<0,05), незначного зниження концентрації T-bet і не впливає на концентрацію GATA3 в Т-хелперах. Введення PTX діабетичним тваринам зменшує кількість T-bet+-клітин у ВПСоВ (на 24-30%, р<0,05), не впливає на щільність Th2 у ворсинках, різноспрямовано змінює їх число в ілВ, дещо знижуючи концентрацію T-betна 4-й тиждень розвитку ецД при відсутності змін концентрації GATA3 в імунопозитивних клітинах. В эксперименте изучалось влияние экспериментального сахарного диабета на интенсивность экспрессии транскрипционных факторов T-bet и GATA иммунными клетками подвздошной кишки. Для определения T-bet+ та GATA +-клеток был использован метод непрямой иммунофлюоресценции с использованием моноклональных антител к T-bet и GATA крыс. Установлено, что развитие диабета сопровождается увеличением количества T-bet+-клеток в лимфоидных структурах кАлТ на 45-72% (р<0,05), снижением суммарной плотности GATA3+-лимфоцитов на 21-44% (р<0,05), незначительного снижения концентрации T-bet и не влияет на концентрацию GATA3 в Т-хелперах. Введение PTX диабетическим животным уменьшает количество T-bet+-клеток в СПСоВ (на 24-30%, р<0,05), не влияет на плотность Th2 в ворсинках, разнонаправленно изменяет их число в илФ, несколько снижая концентрацию T-bet на 4-й неделе развития ЭСД при отстствии изменений концентрации GATA3 в иммунопозитивных клетках. . A considerable quantity of researches of patients with a diabetes and its models at animals have shown a close connection of development type 1 diabetes mellitus and changes in an intestine which anticipate appearance of clinical symptoms of disease. Functional polarization of T-helpers in gut-associated lymphoid tissue plays an important role in an induction of development and progression of T1DM. The great interest represents studying of adaptive immune system, especially tight regulation of the type 1 inflammatory response, at the development of autoimmune disease, such as type 1 diabetes mellitus. Because reduction of an expression of gene GATA3 which is accompanied by weakening of a differentiation of Th2-cells and intensifying of a differentiation of Th1-cells, promotes the development of some Th1 / Th17-dependent autoimmune processes whereas intensifying of its expression can promote development of allergic diseases. Proinflammatory cytokines, such as TNFα play one of the most important roles in pathogenesis of T1DM. Indirect inhibitors of their production (for example, pentoxifylline, PTX) reduce risk of development of this pathology. The aim of research: To study the peculiarities of T-bet and GATA transcriptions factors expression in gutassociated lymphoid tissues (GULT) of rats with experimental STZ-induced diabetes mellitus and pentoxifylline administration. Methods:Researches are made on Wistar rats. For an induction of diabetes streptozotocin was used in doses 50 mg/kg. Structure of population of T-bet+ and GATA +-cells has been studied by the analysis of serial histological sections using the method of indirect immunofluorescense with monoclonal antibodies to T-bet and GATA of rat. T-bet+ and GATA +-cells, which were situated in lamina propria of villi and subepithelial zone of ILF has been studied by coloring of monoclonal antibodies to T-bet and GATA3. It demonstrates features of activation of effector and inductive immune response in GALT. Results: It has been established that diabetes development was accompanied with 45-72% (р <0,05) increase in quantity of T-bet +-cells in lymphoid structures of ileum, with 21-44% (р <0,05) decrease in total density of GATA3+-lymphocyte, an insignificant decrease in concentration of T-bet and it had no influence on concentration of GATA3 in T-helpers. Pentoxifylline administration of diabetic animal reduces the quantity of T-bet+-cells in mucous membrane of villus (on 24-30%, р <0,05), does not influence the density of Th2 in villus, changes their number in ILF, reduces concentration of T-bet by the 4th week of development of T1DM in the absence of concentration changes of GATA3 in immunopositive cell. Conclusions: The expression augmentation with T-bet and GATA in ileum immunopositive cells can influence the differentiation of subsets of T-helpers and their proinflammatory cytokines production, thus acting as one of triggers of diabetes development and progression.
Влияние экспериментального сахарного диабете на экспрессию транскрипционных факторов T-bet и GATA3 в лимфоидных стуктурах подвздошной кишки крыс
Inluence of Experimental Diabetes Mellitus on the T-Bet and Gata Transcriptions Factors Expression in Lymphoid Structures of Ileum in Rats
Keywords: діабет; T-bet; GATA; кишково-асоційована лімфоїдна тканина; диабет; T-bet; GATA; кишечно-ассоциированная лимфоидная ткань; diabetes; T-bet; GATA; gut-associated lymphoid tissue